GGA: 59 indicators, many questions - Njuguna, Lucy (2025)
COP30’s compromise on adaptation indicators positions CGIAR as a vital partner, leveraging its research to transform cautious political agreements into measurable, financeable actions that strengthen global food, land, and nutrition systems against climate change.